2021
DOI: 10.18201/ijisae.2021167932
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Segmentation of QRS Complex on ECG Signals and Classify Cardiovascular Diseases via a Hybrid Model Based on Machine Learning

Abstract: Automated-detecting intelligent programs and methods are developing to find out diseases in medicine in recent years. Developing new methods and improving existing ones are currently ongoing research. One of the most important health problems is heart diseases for all people in the world. Electrocardiography (ECG) is a diagnosis tool that gives substantially functional information about heart and cardiac system. In this work, it is primarily aimed at developing an intelligent system based on ECG signal process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yaman O et al [48] attained 91.25% precision utilizing SVM and KNN approach. Simjanoska et al [49] attained 93.5% accuracy using CNN. Yaman O et al [48] attained 91.25% precision utilizing SVM and KNN approach.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Yaman O et al [48] attained 91.25% precision utilizing SVM and KNN approach. Simjanoska et al [49] attained 93.5% accuracy using CNN. Yaman O et al [48] attained 91.25% precision utilizing SVM and KNN approach.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…e assessment and development of the entire program are to be carried out in the MATLAB 2021a with 11th Gen Intel(R) Core (TM) i5-1135G7 @ 2.40 GHz computer processor, 8.00 GB RAM, and 1 TB hard disk along with also tested on Raspberry Pi 3.0+, Arduino, and heart monitor on run time. Performance evaluation of algorithms is evaluated with different statistical parameters as shown in the following equations adapted from [27][28][29][30][31][32][33]45]:…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…Gelan Ayana et al proposed the ImageNet transfer learning method to detect breast cancer for detection and diagnosis and achieved accuracy better as compared to the previous research [ 24 27 ]. The deep learning approach with the recurrent neural network (RNN) is useful in the ECG rhythm classifier for the sequence modeling of imbalanced data and further compared the performance of the RNN with the long short-term memory (LSTM) and gated recurrent unit (GRU) and observed that the LSTM technique is the latent method for the sequential data with an accuracy of 97.7% [ 28 31 ]. In addition, researchers proposed the validation of ECG-derived sleep architecture and ventilation in sleep apnea and chronic fatigue syndrome and analyzed the result by using the kappa score, which is 0.68, 0.85, and 0.69 for different classes [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%